Agreement With Conjoined NPs Reflects Language Experience - Lorimor, Heidi; Adams, Nora C.; Middleton, Erica L. (Frontiers in Psychology, 2018)
An important question within psycholinguistic research is whether grammatical features, such as number values on nouns, are probabilistic or discrete. Similarly, researchers have debated whether grammatical specifications are only set for individual lexical items, or whether certain types of noun phrases also obtain number valuations at the phrasal level. Through a corpus analysis and an oral production task we show that conjoined noun phrases can take both singular and plural verb agreement and that notional number (i.e., the numerosity of the referent of the subject noun phrase) plays an important role in agreement with conjoined noun phrases. In two written production tasks, we show that participants who are exposed to plural (versus singular or unmarked) agreement with conjoined noun phrases in a biasing story are more likely to produce plural agreement with conjoined noun phrases on a subsequent production task. This suggests that, in addition to their sensitivity to notional information, conjoined noun phrases have probabilistic grammatical specifications that reflect their distributional properties in language. These results provide important evidence that grammatical number reflects language experience, and that this language experience impacts agreement at the phrasal, and not just lexical, level.